Water Weaponisation: The Syrian Case - Margarida Gama (e-cadernos ces)
The start of the twenty-first century has seen the scarcity of water resources being increasingly framed as a weaponised instrument of war and a military objective by multiple actors. This article questions how the weaponisation of water by state actors and non-state actors in a violent conflict can further their hydro‑hegemony and power. It is argued that actors in a violent conflict weaponise water to materialise their war objectives in strategic gains and to (re)position themselves as the hydro‑hegemons of strategic geographical areas allowing them to enhance their power. To support this argument, this research draws on the Syrian conflict, specifically on the fight in the Barada valley and on the framework of hydro‑hegemony.